A review of the management and treatment of brine solutions. Issue 4 (4th May 2017) - Pramanik, Biplob Kumar; Shu, Li; Jegatheesan, Veeriah
Abstract : This paper critically reviews current technologies for concentrate management including emerging membrane technologies, which could recover valuable minerals from brine solutions. Abstract : There has been a considerable expansion in the use of desalination plants for supplying potable water to many communities in the world. However, the production of brine, which is known to be a concentrated solution, is an integral part of the operation of the desalination plant, which faces critical environmental challenges because of its high salinity. Therefore, a cost-effective and environmentally benign brine management system is required prior to its proper disposal. Currently, several disposal options including surface water discharge, deep well injection, and evaporation ponds have been used. However, these processes are unsustainable and their use is limited by a high capital cost and limited applications. Various conventional treatments including physicochemical, oxidation and biological processes with varying extents of organics removal have been reported. Nowadays, membrane-based technologies appear to be cost-effective methods for managing brine concentrate as they can recover valuable resources and produce clean water with high recovery. This paper critically reviews current technologies for concentrate management, including disposal practices and treatment processes. The characteristics of the brine in terms of water quality and its impact on open water bodies are discussed. This paper examines emerging membrane processes such as forward osmosis, membrane distillation, and electrodialysis that show promise for minimizing brine volume, in recovering valuable resources and improvement of water recovery. This paper also discusses the fact that integrated membrane processes are better for brine management for resource recovery together with water purification in wastewater treatment facilities and can achieve a zero liquid discharge.